2014
DOI: 10.1371/journal.pone.0114067
|View full text |Cite|
|
Sign up to set email alerts
|

The Biogeochemical Role of Baleen Whales and Krill in Southern Ocean Nutrient Cycling

Abstract: The availability of micronutrients is a key factor that affects primary productivity in High Nutrient Low Chlorophyll (HNLC) regions of the Southern Ocean. Nutrient supply is governed by a range of physical, chemical and biological processes, and there are significant feedbacks within the ecosystem. It has been suggested that baleen whales form a crucial part of biogeochemical cycling processes through the consumption of nutrient-rich krill and subsequent defecation, but data on their contribution are scarce. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 63 publications
1
73
1
Order By: Relevance
“…The higher Fe/C ratio in the stomach and digestive gland compared to the rest of the body suggests that krill are ingesting more Fe than they require. The Fe/C ratio for whole krill from this study (10.3 ± 4.3 μ mol mol −1 ) is much lower compared to our previous estimate (69.0 μ mol mol −1 in Ratnarajah et al ) based on samples collected at a different location (Table ). Iron‐to‐carbon ratios in whole krill from the recent study are also similar to diatoms (6 μ mol mol −1 ), autotrophic flagellates (8.7 μ mol mol −1 ) and heterotrophic flagellates (14.1 μ mol mol −1 ) growing in Fe deplete conditions (Twining and Baines ).…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The higher Fe/C ratio in the stomach and digestive gland compared to the rest of the body suggests that krill are ingesting more Fe than they require. The Fe/C ratio for whole krill from this study (10.3 ± 4.3 μ mol mol −1 ) is much lower compared to our previous estimate (69.0 μ mol mol −1 in Ratnarajah et al ) based on samples collected at a different location (Table ). Iron‐to‐carbon ratios in whole krill from the recent study are also similar to diatoms (6 μ mol mol −1 ), autotrophic flagellates (8.7 μ mol mol −1 ) and heterotrophic flagellates (14.1 μ mol mol −1 ) growing in Fe deplete conditions (Twining and Baines ).…”
Section: Discussioncontrasting
confidence: 91%
“…The Fe concentrated in krill is transferred to higher order marine animals when they are eaten, and ultimately recycled through the defecation of excess Fe into Fe‐poor surface waters of the Southern Ocean (Nicol et al ; Ratnarajah et al ). Adult whales, like all mammals, do not require all the Fe that they ingest and, because they cannot excrete Fe once it has been absorbed, most of it is defecated (Smetacek ; Nicol et al ; Ratnarajah et al ). Baleen whales take in Fe that is unavailable for phytoplankton growth (because it is locked up in the bodies of krill) and convert it to faecal slurry that could be a stimulant for phytoplankton growth (Smith et al ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also found vast regional differences: Vertical transport capacity in the Southern Ocean is now ∼16% of its historical value, but there are higher values in the North Pacific (34%) and the North Atlantic (28%). We compare our estimates of P movement at natural capacity by marine mammals with quantities of ocean P concentrations that were measured by the Ocean Climate Laboratory (details are provided in SI Appendix) and estimate that on a yearly basis, in the past, marine mammals could have increased surface concentrations by up to 1% per year in the Southern Ocean [2.5 kg·km −2 ·y −1 added to a mean concentration of 248 kg·km −2 , although other calculations have suggested that the effect on trace elements could be even higher (29)], which could result in considerable stock changes in surface P over time.…”
Section: Lateral Nutrient Distribution Capacity By Terrestrial Mammalmentioning
confidence: 99%
“…However, if sea ice is not present, the Fe delivered from glaciers, land masses and sediments will not have the opportunity to be stored over winter and released into surface waters in spring, at a time ideal for phytoplankton growth; i.e., the link that sea ice makes between the continental sources (where Fe is replete) and the offshore high-nutrient low-chlorophyll surface ocean (where Fe is needed) would be cut. Also, higher trophic levels, such as krill and whales that rely on sea ice and its associated food web, have been recognized to play a role in remineralizing Fe in surface waters (Tovar-Sánchez et al, 2007;Lavery et al, 2010;Nicol et al, 2010;Ratnarajah et al, 2014). As such, it will be difficult to predict what effect a predicted reduction in sea-ice extent and volume will have on the Fe cycle given the multiple interlinked positive and negative feedback loops.…”
Section: Effects Of Climate Change On the Cycle Of Fe In Antarctic Wamentioning
confidence: 99%